(untitled) - Smith, Hugh McCormick (Washington, 1945)
The main purpose of this work is to make known, by means of a comprehensive and not too technical account, the nature, exent, and richness of the fish fauna imhabiting the fersh waters of the acinent Kingdom of Siam.
Keywords: Fishes,Freshwater animals,Động vật nước ngọt,Nuôi cá; Thái Lan; Thailand,Thailand